Student’s Perspective On Business Letter Topic: Case Study Of English Education Department Students Of UHKBNP In English Correspondence Subject - Sitanggang, Anita; Nababan, Irene Adryani; Nainggolan, Adika Indotua; Tarigan, Amos Frans Abdial; Simanjuntak, Palti Hand T Maruhum (Innovative: Journal Of Social Science Research, 2025)
This research explores the perspectives of English Education Department students at the University of HKBP Nommensen Pematangsiantar (UHKBNP) on the topic of business letter writing within the English Correspondence subject. Recognizing business letters as essential tools for professional communication, this research investigates students’ attitudes toward their relevance, challenges encountered during learning, and the applicability of these skills in their future careers. Employing a qualitative case study methodology, data were collected through interviews with ten students, focusing on their experiences and insights. Findings reveal that students understand the importance of business letters for professional success, appreciating their role in developing professionalism, critical thinking, and linguistic skills. However, challenges such as mastering formats, adapting tone to context, and limited exposure to real-world applications were identified. Students valued interactive teaching methods and constructive feedback but highlighted the need for improvements, including the integration of technology and practical learning activities. The study underscores the need for curriculum enhancements to align with the evolving demands of digital and professional landscapes. By addressing identified challenges and implementing suggested improvements, this research contributes to optimizing business correspondence education, ensuring students are well-prepared for the communication demands of modern workplaces.